L'autocitation à travers la structure ADV(ment) parlant - Mora, Luisa (Verbum – Analecta Neolatina, 2007)
Taking into account the concept of 'self-citation' as ‘literal reproduction, word by word, of someone's words (cf. the prefix auto-) in order to indicate the right scope to understand sentences', the paper intends to analyse the relation between elements inside the adverbial structure "ADVment parlant" where 'ADVment' is understood as 'point of view adverbs'. The paper presents an analysis of the nature of the relation between the adverbial structure and the sentence which is related to it. A new concept will be introduced - close to what is referred to as the parenthétique character of these adverbs - the parenthésique character, which appears only when they the adverbs are used in final position. There, "self-citation" emerges unleashing a range of cognitive procedures.